Frontiers in Voltammetry - Rajendrachari, Shashanka; Kenchappa Somashekharappa, Kiran; Peramenahalli Chikkegouda, Sharath; Vasanth, Shamanth (IntechOpen, 2023)
This book provides a detailed analysis of recent advances in the various voltammetric techniques used to determine different analytes. It describes the basic concepts of voltammetry and its applications in a simple, easy-to-understand way. The book will suit anyone who wants to learn more about electrochemical sensors, different voltammetric methods, and their advanced applications, including undergraduate, postgraduate and research students.